2014
DOI: 10.1007/s12122-014-9189-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender Wage Gap when Women are Highly Inactive: Evidence from Repeated Imputations with Macedonian Data

Abstract: The objective of this research is to understand if large gender employment and participation gaps in Macedonia can shed some light on the gender wage gap. A large contingent of inactive women in Macedonia including long-term unemployed due to the transition process, female remittance receivers from the male migrant, unpaid family workers in agriculture and so on, is outside employment, but is not necessarily having the worst labour-market characteristics. In addition, both gender wage gap and participation gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Table 2 also supports our discussion: having a child likely makes a difference-mothers are lower paid than childless women and also compared to men (both with or without children). If looking at the unadjusted gaps pattern may suggest a role for motherhood in explaining (part of) the gender wage gap in Macedonia, then we may be able to further explain the adjusted gap seen in Petreski et al (2014). Figures 1 and 2 cross-analyse the gender and motherhood wage gaps, respectively, with the gender/motherhood employment and participation gaps for childbearing-age persons at different levels of education.…”
Section: Some Stylised Factsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 also supports our discussion: having a child likely makes a difference-mothers are lower paid than childless women and also compared to men (both with or without children). If looking at the unadjusted gaps pattern may suggest a role for motherhood in explaining (part of) the gender wage gap in Macedonia, then we may be able to further explain the adjusted gap seen in Petreski et al (2014). Figures 1 and 2 cross-analyse the gender and motherhood wage gaps, respectively, with the gender/motherhood employment and participation gaps for childbearing-age persons at different levels of education.…”
Section: Some Stylised Factsmentioning
confidence: 99%
“…A recent study (Petreski, Mojsoska-Blazevski, & Petreski, 2014) has shown that the gender wage gap in Macedonia-when workers' characteristics and selectivity bias into employment have been taken into account-is ~ 7.5%. This suggests that 7.5% lower wage for women than men, on average, remains unexplained and could be understood as discrimination against women in the labour market.…”
Section: Introductionmentioning
confidence: 99%
“…Length of seeking a job before the current one (now employed) Females are more exposed to low wages (at the left-hand side of the wage distribution, resulting in a negative gender wage gap; see Petreski et al 2014), albeit the peak of their wage distribution is similar to that of males (Figure 6,left). Though, females are also slightly more represented at the high-wage end/tale.…”
Section: Data and Sample Descriptionmentioning
confidence: 99%
“…However, it has been exposed to some criticism (see, e.g. Petreski et al 2014). The first line of criticism is related to the exclusion restrictions, i.e.…”
Section: Missing Wages For Unemployedmentioning
confidence: 99%
See 1 more Smart Citation